“Moving media, that’s what we recommend”: Intermedial Reception in The Square (Ruben Östlund, 2017) - Sebastien Lefait (Interfaces)
Through the analysis of key sequences in the film and more generally of The Square’s unique way of including various media, this article argues that the film purports to place its viewers in a state of confused reception, resulting from the overlapping areas between multiple forms of mediation. It proposes that The Square cleverly ascribes the current inability to identify the boundaries between performance and reality, fiction and non-fiction, etc., to an intermedial type of viewership born from overexposure to different yet similar media forms that include the Internet in general, the viewing platform YouTube in particular, the global surveillance apparatus, television, and of course, ultimately, the art of film itself. It finally argues that the blurring of thresholds prompts a reception mode that is applied to a media continuum that extends from high art to popular culture.